2009
DOI: 10.1038/nchembio.213
|View full text |Cite
|
Sign up to set email alerts
|

How curved membranes recruit amphipathic helices and protein anchoring motifs

Abstract: Lipids and several specialized proteins are thought to be able to sense the curvature of membranes (MC). Here we used quantitative fluorescence microscopy to measure curvature-selective binding of amphipathic motifs on single liposomes 50-700 nm in diameter. Our results revealed that sensing is predominantly mediated by a higher density of binding sites on curved membranes instead of higher affinity. We proposed a model based on curvature-induced defects in lipid packing that related these findings to lipid so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
525
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(559 citation statements)
references
References 50 publications
24
525
3
1
Order By: Relevance
“…Other membrane-binding proteins as well as amphiphilic compounds used in chemical biology might prefer deeper or shallower defects, depending on the amino acid composition of their hydrophobic moiety 35,44,47,48 . These variations, which are also critical in membrane curvature generation mechanisms 49 , are ignored in models where membrane curvature is assumed to simply increase the number of 'binding sites' for peripheral proteins, regardless of the type of hydrophobic moieties 16,17 . Therefore, our atomistic approach should be instrumental to better characterize various modes of protein adsorption on membrane organelles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other membrane-binding proteins as well as amphiphilic compounds used in chemical biology might prefer deeper or shallower defects, depending on the amino acid composition of their hydrophobic moiety 35,44,47,48 . These variations, which are also critical in membrane curvature generation mechanisms 49 , are ignored in models where membrane curvature is assumed to simply increase the number of 'binding sites' for peripheral proteins, regardless of the type of hydrophobic moieties 16,17 . Therefore, our atomistic approach should be instrumental to better characterize various modes of protein adsorption on membrane organelles.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this stress triggers a response characterized by the upregulation of a fatty acid desaturase (Ole1 in yeast) and the arrest of cholesterol synthesis [9][10][11][12] . In addition, several peripheral proteins involved in various functions (lipid transfer, autophagy, nuclear pore formation, vesicle tethering and protein coat dynamics) seem to recognize lipid-packing defects by adsorbing preferentially to positively curved membranes through the insertion of long amphipathic sequences 4,[13][14][15][16][17] .…”
mentioning
confidence: 99%
“…Recently, it has been reported that the bg subunits of G proteins can also sense membrane curvature 57 . The present studies from our laboratory have demonstrated an 'ongoing activation' of Gi-coupled S1P receptors that is necessary for cargo sorting into ILVs destined for exosomal release.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal content quantification assay was performed by fluorescence-based single liposome assay 57 . HeLa cells were seeded at 5 Â 10 5 cells on 60 mm culture dish and cells were transfected with CD63-GFP and indicated siRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, dynamic membrane remodeling is accomplished by the reversible assembly of membrane-deforming proteins (1,2), most notably by members of the Bin/amphiphysin/Rvs (BAR) domain superfamily (3). BAR domains are characterized by α-helical coiled coils that dimerize into modules with a positively charged surface that interacts with phospholipid membranes (4,5).…”
mentioning
confidence: 99%